Preliminary study of macrofungi at UiTM forest reserve, Negeri Sembilan / Suliza Amira Sulaiman - Sulaiman, Suliza Amira (Faculty of Applied Sciences, 2014)
A study was done at UiTM Forest Reserve, Negeri Sembilan to study on macrofungi. The methods used in this study were samples collection, samples identification, samples preservation and samples storage. The objectives of this study were to determine the species compositions and diversity of macrofungi at UiTM Forest Reserve, Negeri Sembilan. The samples of macrofungi were collected randomly at UiTM Forest Reserve, Negeri Sembilan for three times of sampling. In this study, 407 individuals of macrofungi were collected. This comprised of 15 macrofungi families. From this study it was also identified that there were 20 genera of macrofungi at UiTM Forest Reserve, Negeri Sembilan. From this study, it was found the diversity index of macrofungi was H’=1.839, the richness index was R1= 6.794 and evenness index was E=0.31. It was concluded that UiTM Forest Reserve was diverse and rich with macrofungi.